Representation of analytic functions by generalized series of exponents in unbounded convex domains - Krutigolova, Ye. K. (Ukrains’kyi Matematychnyi Zhurnal, 1998)
We establish conditions for the representation of functions f(z) analytic in unbounded convex domains D and continuous in \(\bar D\) via series of the form \(\sum olimits_{n = 1}^∞ {P_n \left( z \right)} e^{λ _n z} \) .